Revising the Formation of β‑Hematin Crystals from Hemin in Aqueous-Acetate Medium Containing Chloroquine: Modeling the Kinetics of Crystallization and Characterizing Their Physicochemical Properties (2023)
ABSTRACT: We investigated the kinetics of conversion of hemin to β-hematin in aqueous-acetate medium in the absence and in the presence of two concentrations of chloroquine by using 11 reported kinetic equations. The two best kinetic equations are the combination of order 1 and Avrami and the combination of second order and logistic equations, based on the statistical parameter variance and overall errors. The best fitted equations are composed of two terms from which we model the formation of β-hematin as the result of two processes: the availability of reactive precursors and the formation of nucleation and growth sites. The crystals exhibit needle-like morphologies about 760-nm-long and 140-nm-wide. However, the increment of chloroquine favors the formation of crystal twinning with nonhomogenous distribution, crystals with lower sizes of similar heights and widths, and crystals symmetrically tapered at the ends of the needles. The lattice volumes, obtained from Rietveld analysis of powder X-ray diffraction patterns, were not regularly affected by chloroquine. The main IR absorption bands did not appreciably change in positions nor in intensities with varying chloroquine concentration. However, important changes were observed in the 2000–4000 cm–1 region. We used density functional theory calculations to understand these changes.